The Cambridge Introduction to modernist poetry - Howarth, Peter, 1973- (Cambridge introductions to literature., 2012)
"Modernist poems are some of the twentieth-century's major cultural achievements, but they are also hard work to read. This wide-ranging introduction takes readers through modernism's most famous poems and some of its forgotten highlights to show why modernists thought difficulty and disorientation essential for poetry in the modern world. In-depth chapters on Pound, Eliot, Yeats and the American modernists outline how formal experiments take on the new world of mass media, democracies, total war and changing religious belief. Chapters on the avant-gardes and later modernism examine how their styles shift as they try to re-make the community of readers. Howarth explains in a clear and enjoyable way how to approach the forms, politics and cultural strategies of modernist poetry in English"--